“Silenciada fui, poesia sou”: narrativas poéticas de mulheres negras da cena do slam no interior cearense - Oliveira, Geovana Dara Pereira de (2023)
This dissertation discusses the intersections of poetry and writing in the identity processes of black women who are part of the slam scene in the Ceará region. Its methodology involved a study of life history narratives and an intersectional analysis based on the accounts of two black women poets participating in the slam scene. The theoretical framework predominantly comprises works by black authors within the field of black feminism. It weaves discussions from an intersectional perspective about the silencing of black women, writing as a tool of resistance, processes of community building through cultural movements, and the lived experience of the poet as an identity. This is viewed through the lens of Critical Social Psychology, which aims to challenge the fetishized and annihilating perspectives imposed on the experiences of black women.